Narrevivências de pessoas pretas - Valdiceia Miranda Machado Bouzada (2024)
Racism impacts on the mental health of the black population, not considering its effects on people's subjectivity, it constitutes an act of violence, once the processes of illness are collective and occur in the field of occupational processes, with the narrative being a “taking care of oneself”, which enables awareness of one’s own existence, permission for transformations. Objective: To verify the configurations of experiences of racism, discrimination, prejudice and the relationship with the mental health of black people using mental health services in the city of Belo Horizonte by listening to narratives from their daily lives. Research trajectory: It is a qualitative study. It was carried out by sharing with 19 people, black men and women, users of CERSAM - Centro de Referência em Saúde Mental de Belo Horizonte - Belo Horizonte Mental Health Reference Center. Data collection took place through individual meetings. The narratives are organized as “narrreviências”, paraphrasing Conceição Evaristo’s “escrevivências”. Discussion: The narrreviências bring a path of pain that crosses a collective of bodies deprived of a social place. The discussions revolve around interracial family relationships; family abandonment, the relationship with power devices; violence against women; issues of race and the discourse of racial democracy; hypermedicalization; and last but not least, the issue of research neutrality. Results: This study proposes reflections that point to the responsibilities of health professionals in relation to the manifestation of ethnic-racial issues and oppression in clinical practice, as well as affirming the importance of ethically racialized listening, attentive to the violation of rights and threats to the mental health of the black population